2022
DOI: 10.3390/plants12010112
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Antidiabetic Potential of Cleistocalyx nervosum var. paniala Fruit Extract

Abstract: Diabetes mellitus is a complex global public health condition. Medicinal plants are significant resources in the research of alternative new drug active compounds. Cleistocalyx nervosum var. paniala (C. nervosum) is an indigenous berry fruit widely grown in Southeast Asia. The fruit of C. nervosum exhibit various medicinal properties and health benefits. This study aimed to investigate antidiabetic properties of C. nervosum fruit extract by in vitro assays and in vitro models. C. nervosum fruit extracted using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…The leaf extract of C. operculatus has shown α-glucosidase inhibitory action with an IC 50 value of 0.11 mg/g [22]. Furthermore, Chukiasiri et al (2022) revealed that the plant's fruit extract has a good ability to inhibit α-amylase and α-glucosidase, with IC 50 values of 0.42 and 0.23 g/mL, respectively [23]. In addition, pharmacological studies showed that the C. operculatus extracts had positive effects on streptozotocin-diabetic rats, such as reduced blood glucose levels and protective activities on the β-cells of pancreatic islets [24,25].…”
Section: In Vitro α-Glucosidase Inhibitory Activity Of C Operculatus ...mentioning
confidence: 99%
“…The leaf extract of C. operculatus has shown α-glucosidase inhibitory action with an IC 50 value of 0.11 mg/g [22]. Furthermore, Chukiasiri et al (2022) revealed that the plant's fruit extract has a good ability to inhibit α-amylase and α-glucosidase, with IC 50 values of 0.42 and 0.23 g/mL, respectively [23]. In addition, pharmacological studies showed that the C. operculatus extracts had positive effects on streptozotocin-diabetic rats, such as reduced blood glucose levels and protective activities on the β-cells of pancreatic islets [24,25].…”
Section: In Vitro α-Glucosidase Inhibitory Activity Of C Operculatus ...mentioning
confidence: 99%
“…T2D is thought to result from both insulin deficiency and insulin resistance . There have been many therapies against T2D, such as metformin, pioglitazone, acarbose, glibenclamide, and so on. Natural products have many advantages for T2D treatment, such as preferable biosafety, multifunction, and multiple active sites . Therefore, natural products are thought to be important for new-drug discovery …”
Section: Introductionmentioning
confidence: 99%